2006
DOI: 10.1073/pnas.0605801103
|View full text |Cite
|
Sign up to set email alerts
|

Amber from western Amazonia reveals Neotropical diversity during the middle Miocene

Abstract: Tertiary insects and arachnids have been virtually unknown from the vast western Amazonian basin. We report here the discovery of amber from this region containing a diverse fossil arthropod fauna (13 hexapod families and 3 arachnid species) and abundant microfossil inclusions (pollen, spores, algae, and cyanophyceae). This unique fossil assemblage, recovered from middle Miocene deposits of northeastern Peru, greatly increases the known diversity of Cenozoic tropical-equatorial arthropods and microorganisms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 23 publications
2
48
0
Order By: Relevance
“…First, work on estimating the time of origin of groups that may represent pre-Oligocene relicts should be continued to confirm or falsify the Darwinian nature of New Caledonia. Second, fossil diversity for many groups, including insects, must be better studied, as it can shed light on past diversity and ecosystem history (Antoine et al 2006). In this regard, some studies have revealed a recently extinct large vertebrate fauna, showing that generalizations based only on extant faunas can sometimes be misleading (Gaffney et al 1984;Balouet & Buffetaut 1987;Balouet & Olson 1989).…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…First, work on estimating the time of origin of groups that may represent pre-Oligocene relicts should be continued to confirm or falsify the Darwinian nature of New Caledonia. Second, fossil diversity for many groups, including insects, must be better studied, as it can shed light on past diversity and ecosystem history (Antoine et al 2006). In this regard, some studies have revealed a recently extinct large vertebrate fauna, showing that generalizations based only on extant faunas can sometimes be misleading (Gaffney et al 1984;Balouet & Buffetaut 1987;Balouet & Olson 1989).…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…Ten million years later, just prior to establishment of the transcontinental Amazon River drainage, this inland ecosystem attained huge size (more than 1 million km 2 ) and extreme complexity with multiple environments, such as lakes, embayments, swamps and rivers that drained towards the Caribbean [2,3]. The exceptional depositional and fossil record of the Pebas/Solimões Formations around the Peruvian -Colombian-Brazilian junction permits detailed reconstructions of these Miocene palaeoenvironments and their distinctive biotas [2,[4][5][6][7][8]. Aquatic invertebrates (ostracods and molluscs) are extremely abundant and diverse within those deposits [2,4,[9][10][11],…”
Section: Introductionmentioning
confidence: 99%
“…Deposits of fossil resins are therefore considered exceptional Lagerstätten (2) that provide important data on the paleoecology of Triassic to Neogene forests (3)(4)(5)(6)(7)(8). The presence of marine organisms in tree resin, however, seemed highly unlikely, and the absence of marine inclusions, which could serve as index fossils for dating of amber, had been emphasized in previous literature (6).…”
mentioning
confidence: 99%